THE IMAGE OF THE BORGIA IN THE EARLY TWENTY-FIRST CENTURY. - ROIG, ALBERT CASSANYES (Imago Temporis. Medium Aevum, 2024)
Despite the relevance of the Borgia family, a black legend has been attached to them for five hundred years. The vision of Rodrigo Borgia and his children, notably Cesare and Lucrezia, has tended to be negative in the various works inspired by their history. This work analyses three audio-visual products of different kinds (a film, a series and a video game) from the early twenty-first century to determine which conception of the Borgia family has been transmitted to the millions of people who have used them. This enables us to see if a new Borgia idea is offered or if the one given by their black legend is still maintained.